Income Tax Calculation Application 21: Case Study of a Company in The Field of Door Closer Production and Management in Bandung - Calissa S, Tazkya; Syukri, Muhammad; Parghani, Rizal; Alfiyasin, Feri (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
According to Law No. 36 of 2008 on Income Tax, Income Tax (PPh) is a tax that individuals and corporations must pay based on the total annual income they receive. Deficiencies in the data management process have been highlighted by researchers, specifically in the calculation of income tax, which still needs to be included in an application. Bandung's production and management firm utilizes semi-computerized methods, specifically Excel, for income tax calculations. However, the company still needs to optimize its current computerized system fully. As a result, both the process of gathering data and calculating income taxes need to be improved in effectiveness and efficiency, resulting in time-consuming procedures for retrieving data. Hence, there is a requirement for application software to facilitate the computation of Income Tax, thereby optimizing activities and operational procedures. Therefore, this study is named